COVID-19 and cesarean section rates: A retrospective observational study at our rural tertiary center using robson's classification - Shreya Mor; Shuchi Jain; Poonam Varma Shivkumar; Manish Jain (Apollo Medicine)
Objective: This study aimed to evaluate the effect of COVID-19 infection on the rate and indications for cesarean section (CS) according to Robson's Ten-Group Classification system. Methodology: Our study was a 6-month retrospective observational study at the Maternal and Child Health Wing where every antenatal woman who was admitted irrespective of gestational age and whether in labor or not was customarily screened for COVID-19 infection. Based on the mode of delivery, all delivered women were classified into two groups: vaginal or cesarean, and the information was then further classified according to Robson's classification. Data collected were analyzed using Excel sheets, and Chi-square test was applied to evaluate if the difference in CS rates was statistically significant. Results: During COVID months, a total number of confinements were 877, among which the cesarean section were 381, contributing to a rate of 43.4%. The total COVID-19-positive confinements during the same period were 68. Group 2 formed the vast majority of CSs, followed by Group 1 and 5. During the post-COVID months, summation of confinements was 1443, among which the CS were 580, thereby contributing to a rate of 40.1%. In contrast to COVID time, Group 5 formed the greatest chunk contributing to CS rate, followed by Group 2 and 1. There was a statistically significant difference among confinements during COVID and post-COVID period and between CS rates among COVID-19 positive and negative women. Conclusion: During the COVID pandemic, there was a decrease in the number of confinement in our hospital. However, the CS rate increased and according to Robson's classification Group 1 and 2 made greatest contribution to CSs due to changed dynamics.